2018
DOI: 10.1093/jas/sky236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing management in brachiaria grass-forage peanut pastures on canopy structure and forage intake1

Abstract: Maintenance of mixed grass-legume pastures for stand longevity and improved animal utilization is a challenge in warm-season climates. The goal of this study was to assess grazing management on stand persistence, forage intake, and N balance of beef heifers grazing mixed pastures of Brachiaria brizantha and Arachis pintoi. A two-year experiment was carried out in Brazil, where four grazing management were assessed: rest period interrupted at 90%, 95%, and 100% of light interception (LI) and a fixed rest period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 42 publications
2
64
0
Order By: Relevance
“…In light interception experiments, researchers associate LI with the pre-grazing canopy height once canopy height has a high correlation with LI and it is easy to measure in farm conditions (Gomes et al, 2018;Sbrissia & Silva, 2008). In on-farm conditions, we recommend the pre-grazing height of 26 cm that correspond to 95% of LI.…”
Section: Discussionmentioning
confidence: 99%
“…In light interception experiments, researchers associate LI with the pre-grazing canopy height once canopy height has a high correlation with LI and it is easy to measure in farm conditions (Gomes et al, 2018;Sbrissia & Silva, 2008). In on-farm conditions, we recommend the pre-grazing height of 26 cm that correspond to 95% of LI.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from the results that there was a gradual increase in the proportion of legume in the sward and a concomitant increase in animal performance ( Figure 6). In general, the legume proportion in ruminant diets is proportional to their contribution to the botanical composition (Curll, Wilkins, Snaydon & Shanmugalingam, 1985;Gomes et al, 2018). Thus, a greater legume proportion than of grass resulted in greater nutritive value and improved animal performance.…”
Section: Discussionmentioning
confidence: 99%
“…The botanical composition data (BC; proportion of legume in the herbage mass) used in this study can be found in Gomes et al. (2018).…”
Section: Methodsmentioning
confidence: 99%